Optimization of Reaction Conditions for Synthesis of MOF-5 using Solvothermal Method - Mulyati, Tri Ana; Ediati, Ratna; Nadjib, Muhammad (Institut Teknologi Sepuluh Nopember, 2014)
MOF-5 (metal-organic frameworks-5) have been synthesized using solvotermal method in which reaction mixtures of zinc nitrate hexahydrate and benzenedicarboxylic acid in dimethylformamide were heated at various heating temperatures and times in order to obtain the best reaction conditions for the synthesis of MOF-5. The heating temperatures used were 105, 120 and 140 °C, respectively with heating times of 12-144 hours. Determination of the best reaction conditions was based on the observation of phase purity and crystal morphology of MOF-5 using XRD and SEM. The characterization results showed that optimization of MOF-5 crystals were obtained when the reaction mixtures were heated at 105 °C for 144 h, 120 °C for 24 h and 140 °C for 12 h. The maximum weight of MOF-5 crystal was generated from reaction mixture heated at 120 °C for 72 h.